2005
DOI: 10.1093/ageing/afi179
|View full text |Cite
|
Sign up to set email alerts
|

A whole system study of intermediate care services for older people

Abstract: This city-wide IC service was associated with similar clinical outcomes but did not achieve its strategic objectives of reducing long-term care and hospital use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 11 publications
1
34
0
1
Order By: Relevance
“…In an evaluation of a city-wide IC service within the UK, older patients (nϭ848, median age 85 years) presenting with falls, confusion, incontinence or immobility to an elderly medicine department were compared to historical controls. 43 Only 29% of these patients received any IC service (mainly HaH). Functional outcomes, institutionalisation rates and mortality were similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of a city-wide IC service within the UK, older patients (nϭ848, median age 85 years) presenting with falls, confusion, incontinence or immobility to an elderly medicine department were compared to historical controls. 43 Only 29% of these patients received any IC service (mainly HaH). Functional outcomes, institutionalisation rates and mortality were similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may not necessarily mean lower cost, particularly if undertaken within acute hospital environments. [9][10][11] There is often a high degree of substitution between these different forms of care, reflecting differences in clinical management of patients, in administrative processes including type-changing between different episodes of care and in the availability of appropriate treatment settings for each type of care, particularly in rural areas.…”
Section: Definition Of Subacute Carementioning
confidence: 99%
“…While some studies have reported substantial challenges in the implementation process, [6] others have found significant decreases, not only in admission rates, costs and admission lengths, [7][8][9] but also in readmission rates. [10] A number of other studies, despite findings of increased costs, [11,12] report no significant impact on admission [1,2,13] and readmission rates. [14,15] The inconsistent findings may be due to the fact that the care of frail elderly citizens has multiple stakeholders, with different jurisdictions (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…There is a growing body of evidence that suboptimal hospital care and treatment of frail elderly patients with complex medical issues are caused by short and compressed admissions [1,2] and by the loss of information in the transition from hospital to community care. [3] These problems are increasingly addressed through new forms of health care delivery, such as intermediate care interventions, traditionally targeting elderly people.…”
Section: Introductionmentioning
confidence: 99%